Pyrroloquinoline quinone (PQQ) alleviated sepsis-induced acute liver injury, inflammation, oxidative stress and cell apoptosis by downregulating CUL3 expression. Issue 1 (1st January 2021) - Wu, Yanhong; Zhao, Meiling; Lin, Zhaoheng
ABSTRACT: PQQ has anti-inflammatory and anti-oxidant effects. PQQ can relieve high glucose-induced renal cell damage by suppressing Keap1 expression. Keap1 can interact with CUL3. Upregulation of CUL3 facilitates the apoptosis of LPS-induced podocytes. Based on knowledge above, this current work was designed to explore the role of PQQ in sepsis and determine the molecular function of CUL3 in the pathogenesis of sepsis. Rats received CLP surgery to establish sepsis models in vivo. Kupffer cells were pretreated with PQQ (10, 50 and 100 nmol/L) for 2 h and then treated with 100 ng/mL LPS for 24 h, simulating sepsis-induced acute liver injury in vitro. H&E staining was performed to evaluate liver injury of SD rats. Levels of inflammatory factors and oxidative stress markers were detected to assess inflammatory response and oxidative stress. Moreover, TUNEL staining, flow cytometric analysis and western blot were applied to determine cell apoptosis. It was confirmed that PQQ treatment relieved acute liver injury, inflammatory and oxidative stress damage and apoptosis of liver tissue cells in sepsis rats. In addition, PQQ therapy could alleviate inflammation, oxidative stress and apoptosis in LPS-induced Kupffer cells. Notably, LPS stimulation enhanced CUL3 expression and PQQ repressed CUL3 expression in Kupffer cells suffered from LPS. Overall, CUL3 overexpression weakened the remission effects of PQQ on LPS-induced inflammatory and oxidative damage and apoptosis of Kupffer cells. Mechanistically, PQQ treatment may mitigate sepsis-induced acute liver injury through downregulating CUL3 expression. Graphical Abstract: uf0001